A Case Report of Nongerminal Center B-Cell Type Diffuse Large B-Cell Lymphoma Treated to Complete Response with Rituximab and Ibrutinib - Geoffrey Shouse; Miemie Thinn (Case Reports in Hematology)
Diffuse large B-cell lymphoma (DLBCL) is a molecularly heterogeneous disease consisting of different subtypes with varying clinical behaviors. For example, the activated B-cell-like (ABC) type of DLBCL has lower cure rates with traditional chemotherapy regimens. The molecular pathway promoting tumorigenic growth of the ABC type includes a dependence on intracellular signaling by Bruton’s agammaglobulinemia tyrosine kinase (BTK). This specific pathway has led to the investigation of the utility of ibrutinib in treatment of this type of lymphoma at relapse or in combination with standard chemotherapy. In elderly patients stricken with this disease, standard combination chemotherapy can pose significant toxicity. Some reduced intensity regimens have activity but significantly less favorable long-term outcomes and still pose significant toxicity to elderly patients. In the following case, we demonstrate induction of complete response in an elderly patient with significant comorbidities with nongerminal center B-cell type (NGCB) DLBCL treated with rituximab, ibrutinib, and prednisone. Toxicity included atrial fibrillation that ultimately led to heart failure as well as sepsis which ultimately led to the patient’s demise. Despite this fact, the response to treatment appeared durable. This case illustrates the utility and limitations of molecularly targeted therapies to treat aggressive lymphoma in frail elderly patients.